2017
DOI: 10.1186/s12885-017-3884-2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of differentially expressed genes associated with PLK1 in bladder cancer

Abstract: BackgroundThe significance of PLK1 (polo-like kinase 1) has become increasingly essential as both a biomarker and a target for cancer treatment. Here, we aimed to determine the downstream genes of PLK1 and their effects on the carcinogenesis and progression of bladder cancer.MethodsSpecific siRNA was utilized to silence the target gene expression. The cell proliferation, invasion and migration of bladder cancer cells by MTT assay, BrdU assay and transwell assay. The differential expression genes were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…While this study focused primarily on BORA, our transcriptomic data uncovered multiple pathways previously linked to activated-PLK1 functions. For instance, a gene expression microarray analysis of PLK1 knockdown in bladder cancer cells [50] revealed GO biological processes, such as cell cycle, focal adhesions, VEGF and NF-κB signaling pathways deregulated, similar to what we found in our transcriptomic analysis, hence underlying most of the pathways modulated by BORA are PLK1-dependent. Increasing evidence also supports that PLK1 has multiple nonmitotic functions in cancerous and noncancerous cells [51].…”
Section: Discussionsupporting
confidence: 82%
“…While this study focused primarily on BORA, our transcriptomic data uncovered multiple pathways previously linked to activated-PLK1 functions. For instance, a gene expression microarray analysis of PLK1 knockdown in bladder cancer cells [50] revealed GO biological processes, such as cell cycle, focal adhesions, VEGF and NF-κB signaling pathways deregulated, similar to what we found in our transcriptomic analysis, hence underlying most of the pathways modulated by BORA are PLK1-dependent. Increasing evidence also supports that PLK1 has multiple nonmitotic functions in cancerous and noncancerous cells [51].…”
Section: Discussionsupporting
confidence: 82%
“…NDC80 is a downstream gene of polo-like kinase 1, which is a well-documented oncogene that serves a key role in cell reproduction and invasion (42). In bladder cancer, NDC80 was associated with the regulation of cell reproduction, migration and invasion, and was positively associated with metastasis (43). All of these results suggested that NDC80 serves an important role in the metastases of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, microarrays contingent on high-throughput platforms have emerged as a promising and efficient tool for screening significant genetic or epigenetic alternations in carcinogenesis and identifying promising biomarkers for diagnosis and prognosis of cancers [ 22 ]. Plentiful gene expression profiling microarrays have been employed to identify multifarious differentially expressed genes (DEGs) in various cancers, and a number of BC-related DEGs have therefore been documented [ 23 25 ]. Nonetheless, various additional critical genes and pathways associated with BC remain yet to be explored completely.…”
Section: Introductionmentioning
confidence: 99%